Numerical Simulation of Mould Filling Process in Resin Transfer Moulding - Lam, Yee Cheong (2015)
This paper presents a simulation procedure for the mould-filling processes in which a field-analysis module of a general-purpose finite-element package is employed. The formulations used in this procedure are based on the finite element/nodal control-volume approach. The numerical concepts employed for modelling the effects of convective heat transfer on temperature and resin cure are discussed. Numerical implementation of the procedure is presented. The procedure was applied to simulate different mould-filling examples under isothermal and non-isothermal conditions. The results show that the simulation procedure developed is numerically valid and stable, and provides reasonably accurate predictions.